2022
DOI: 10.3390/brainsci12101403
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Pharmacological and Non-Pharmacological Interventions for the Inflammatory Mechanism of Unipolar Depression

Abstract: Since depression remains a major public health issue there is a constant need for new and more efficient therapeutic strategies based on the mechanisms involved in the aetiology of depression. Thus, the pathogenic link between depression and inflammation is considered to play a potential key role in the development of such therapies. This review summarizes the results of various pharmacological (non-steroidal anti-inflammatory drugs, aspirin, cyclooxygenase inhibitors, cytokine inhibitors, corticosteroids, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 211 publications
0
10
0
Order By: Relevance
“…When studying chronic NAC administration in murine models, Wright et al noted an antidepressant-like effect on both wildtype and Huntington-disease murine models, which was noted to be due to decreased mitochondrial oxidative stress [ 33 ]. Further assessing the potential uses of NAC in depression, various studies assessing depression using the Montgomery–Asberg Depression Rating Scale (MADRS) have observed NAC administration to improve depressive symptoms [ 34 , 35 , 36 ]. These studies suggest a potential for NAC administration as an adjunct therapeutic in MDD.…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…When studying chronic NAC administration in murine models, Wright et al noted an antidepressant-like effect on both wildtype and Huntington-disease murine models, which was noted to be due to decreased mitochondrial oxidative stress [ 33 ]. Further assessing the potential uses of NAC in depression, various studies assessing depression using the Montgomery–Asberg Depression Rating Scale (MADRS) have observed NAC administration to improve depressive symptoms [ 34 , 35 , 36 ]. These studies suggest a potential for NAC administration as an adjunct therapeutic in MDD.…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…The classical antidepressant hypothesis, known as the monoamine theory, uses monoamine oxidase inhibitors (MAOIs) and selective serotonin reuptake inhibitors (SSRIs) to restore low monoamine levels in the brain [ 48 ], while serotonin and norepinephrine reuptake inhibitors (SNRIs) are also used to treat MDD [ 49 ], but individual response varies significantly. Long-term follow-up studies have identified a higher risk of weight gain in individuals prescribed antidepressants, highlighting the need for personalized treatment approaches that consider an individual’s BMI or adiposity [ 50 ].…”
Section: Mdd Stress and Neuropsychoimmunitymentioning
confidence: 99%
“…Unipolar depression (Major Depressive Disorder-MDD) has generally been found to stimulate a pro-inflammatory Th1 response (IL-1, IL-2, soluble IL-2 receptor (-sIL-2R), IL-6, C-Reactive Protein (CRP), TNF-α, and IFN-γ), with a subsequent increase in tryptophan catabolites (the kynurenine pathway) [17,22,23]. Cytokines can be produced by astrocytes and microglia in the brain or diffuse to the brain from the periphery through a leaky blood-brain barrier (BBB), active transport, endothelial cell activation, cytokine receptor binding, or via vagus nerve interaction in the gut, especially when cytokine levels are elevated [21].…”
Section: Immunology Microbes and Psychiatric Disordersmentioning
confidence: 99%
“…Therefore, elevated pro-inflammatory cytokine levels reduce frontal brain activity [19], which may lead to symptoms of depression in immunogenetically susceptible patients [11]. Indeed, depression treatment significantly decreases the levels of some cytokines, including IL-1 [25], and treatment with anti-inflammatory substances, such as minocycline or N-acetyl cysteine (NAC) [22], may improve clinical outcomes in depression.…”
Section: Immunology Microbes and Psychiatric Disordersmentioning
confidence: 99%